Europeizacja nadzoru bankowego w Polsce - Urbaniak, Jarosław (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
Banking supervision is a form of state interventionism applied by this state to express its intention to exercise control over the safety and appropriate functioning of banking system. Membership of the EU has created a new situation in the operation of banking supervision. After the process of harmonization of Polish supervisory solutions was successfully completed, the supervision started to operate under the new circumstances, regulated by the principles of the uniform European financial market. As of January 1, 2008, banking supervision has been vested with the Polish Financial Supervision Authority (KNF). The experience of financial crisis has revealed significant deficiencies in financial supervision, mainly banking supervision. Therefore, the European Commission has decided to accelerate the pace with which financial supervision in the European Union is implemented.